Orthopedic Rehabilitation of Adults with Congenital Cleft Lip and Palate with Combined Orthopedic Constructs (Clinical Observation) - Oliinyk М. Ю.; Oliinyk Г. В.; Hula А. М. (Actual Dentistry, 2025)
Relevance. Patients with congenital cleft lip and palate require long-term dental care involving many specialists, and the completion of treatment is considered to be their prosthetic rehabilitation. After qualified assistance from a surgeon, orthodontist, speech therapist and other specialists, the completion of treatment is carried out by an orthopedic dentist. It is believed that the first stage of orthopedic treatment is manufacturing of a temporary orthopedic structure, which is subsequently replaced by a more advanced fixed or combined structure. Aim: to present a clinical observation of orthopedic rehabilitation of a patient with congenital cleft lip and palate after surgical interventions. Material and methods. Dental clinical and radiological examination methods, as well as photo documentation, were applied. Conclusion. The presented clinical observation demonstrates the high possibility of rehabilitation of patients with congenital cleft lip and palate using orthopedic methods by manufacturing combined orthopedic structures for their occlusal, functional and final rehabilitation, as one of the ways to improve the quality of life of such patients.